Dangerous invasive view Miscanthus sinensis - Skrypnyk, N. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
Due to international trade, there is a real danger moving invasive species to Ukraine. In recent years, in search of a solution to the energy problem, the special attention of scientists is concentrated on a plant of miscanthus, which is new for Ukraine. The glory of this plant is extraordinary. The summary of Miscanthus sinensis are described. It is established that the species is not discerning conditions of growth, sometimes leaving decorative plantations forming large groups, along disturbed zones, displacing local vegetation. The grass is also extremely flammable, which increases the risk of fire in captured areas. The ways of its penetration into the territory of Ukraine are found out.